The mediating effect of resilience on pregnancy stress and prenatal anxiety in pregnant women - Tuxunjiang, Xiabidan; Li, Ling; Wumaier, Gulijianati; Zhang, Wei; Sailike, Bahedana; Jiang, Ting (Frontiers in Psychiatry, 2022)
Objective To investigate the relationship between pregnancy stress and prenatal anxiety in pregnant women in Urumqi, Xinjiang, and the mediating effect of mental resilience level on the relationship between pregnancy stress and prenatal anxiety. Method investigating a 3 armour hospital 750 cases of pregnant women in urumqi, includes the general demographic information questionnaire, the pregnancy stress scale (pregnancy pressure scale, PPS), generalized anxiety disorder scale (generalized anxiety disorder - 7, GAD - 7),Mental resilience scale (Connor – Davidson resilience scale, CD - RISC) questionnaire. Bootstrap mediation effect test was used to test the effect relationship between variables, and Amos was used to establish the structural equation model. Results Among 750 subjects, 122 (16.2%) had moderate or above pregnancy stress (PPS>1), 372 (49.6%) had mild or above anxiety symptoms (GAD-7>5), and 241 (32.1%) had good or above mental resilience score. Pregnancy stress negatively affected resilience (β=-0.37, P<0.01), and resilience also negatively affected prenatal anxiety (β=-0.12, P<0.01).The mediating effect value of resilience was 8.3%.Conclusion Pregnancy stress, mental resilience and prenatal anxiety are significantly correlated, and mental resilience plays a partial mediating role in the influence of pregnancy stress on prenatal anxiety. It is suggested to exercise the mental resilience of pregnant women, so as to reduce the incidence of prenatal anxiety and promote the physical and mental health of pregnant women.